1984
DOI: 10.1104/pp.76.3.823
|View full text |Cite
|
Sign up to set email alerts
|

Injury, Stomatal Conductance, and Abscisic Acid Levels of Pea Plants following Ozone plus Sulfur Dioxide Exposures at Different Times of the Day

Abstract: ABSTRACIPea (Pisum sativum L. cv Alsweet) plants were exposed to mixtures ofozone plus sulfur dioxide at different times of the day. InJury, evaluated either as necrosis or chlorophyll, was greatest at midday when stomatal conductance was greatest. Abscisic acid levels were similar over the day, and showed no relation to stomatal conductance.Investigations of pollutant exposure at different times of the day have been undertaken with 03 and SO2 singly (5). As early as 1949, Katz (10) showed that barley and alf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 18 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…However, our results did not support this process. In fact, several studies also reported no increase of ABA concentration after O 3 exposure (Kobriger et al, 1984;Mao et al, 2017). Foliar ABA contents increased in N80 treated poplar leaves.…”
Section: Effects Of Ozone Nitrogen and Phosphorus On Leaf Ethylene Em...mentioning
confidence: 96%
“…However, our results did not support this process. In fact, several studies also reported no increase of ABA concentration after O 3 exposure (Kobriger et al, 1984;Mao et al, 2017). Foliar ABA contents increased in N80 treated poplar leaves.…”
Section: Effects Of Ozone Nitrogen and Phosphorus On Leaf Ethylene Em...mentioning
confidence: 96%